PENGARUH KERAGAMAN PRODUK, KEPERCAYAAN DAN BRAND IMAGE TERHADAP MINAT BELI ULANG YANG DIMEDIASI KEPUASAN KONSUMEN PADA TOKO CERIA ELEKTRONIK DAWUHAN SITUBONDO - Novansyah, Roby Tri; Praja, Yudha; Minullah, Minullah (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The purpose of the study was to determine the effect of Product Diversity, Trust and Brand Image on Repurchase Interest Mediated by Consumer Satisfaction at the Ceria Elektronik Dawuhan Situbondo Store. The sampling technique used in this study was simple random sampling of 92 consumers. Data analysis and hypothesis testing in this study used Structural Equation Model – Partial Least Square (PLS-SEM) The results showed that Product diversity has a significant effect on Consumer Satisfaction, Trust has a significant effect on Consumer Satisfaction, Brand Image has a significant effect on Consumer Satisfaction, Product diversity has a negative but significant effect on Repurchase Intention, Trust has a positive but not significant effect on Repurchase Intention, Brand Image has a significant effect on Repurchase Intention., Consumer satisfaction has a significant effect on Repurchase Intention, Product diversity has a significant effect on Repurchase Intention through Consumer Satisfaction, Trust has a significant effect on Repurchase Intention through Consumer Satisfaction, Brand Image has a significant effect on Repurchase Intention through Consumer Satisfaction